2021
DOI: 10.12998/wjcc.v9.i24.7032
|View full text |Cite
|
Sign up to set email alerts
|

Case series of COVID-19 patients from the Qinghai-Tibetan Plateau Area in China

Abstract: BACKGROUND Coronavirus disease 2019 (COVID-19) is a serious infection caused by the new coronavirus severe acute respiratory syndrome coronavirus 2. The disease was first identified in December 2019 and has caused significant morbidity and mortality worldwide. AIM To explore the clinical characteristics and treatments for COVID-19 in the Qinghai-Tibetan Plateau Area in China. METHODS We retrospectively analyzed the blood cell counts (neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…An epidemiological investigation by Arias Reyes et al (2020) has revealed a decreased reported incidence of COVID-19, implying a possible weak transmission rate of severe SARS-CoV-2 among highland people [16]. Likewise, in the Tibetan Plateau of China, researchers reported a very modest persistent COVID-19 infection [17].…”
Section: High Altitude Decreased Covid-19: a Dilemmatic Implementationmentioning
confidence: 99%
“…An epidemiological investigation by Arias Reyes et al (2020) has revealed a decreased reported incidence of COVID-19, implying a possible weak transmission rate of severe SARS-CoV-2 among highland people [16]. Likewise, in the Tibetan Plateau of China, researchers reported a very modest persistent COVID-19 infection [17].…”
Section: High Altitude Decreased Covid-19: a Dilemmatic Implementationmentioning
confidence: 99%